Modulation of spinal cord synaptic activity by tumor necrosis factor α in a model of peripheral neuropathy - Spicarova, Diana; Nerandzic, Vladimir; Palecek, Jiri (Journal of neuroinflammation, 2011)
BACKGROUND: The cytokine tumor necrosis factor α (TNFα) is an established pain modulator in both the peripheral and central nervous systems. Modulation of nociceptive synaptic transmission in the spinal cord dorsal horn (DH) is thought to be involved in the development and maintenance of several pathological pain states. Increased levels of TNFα and its receptors (TNFR) in dorsal root ganglion (DRG) cells and in the spinal cord DH have been shown to play an essential role in neuropathic pain processing. In the present experiments the effect of TNFα incubation on modulation of primary afferent synaptic activity was investigated in a model of peripheral neuropathy. METHODS: Spontaneous and miniature excitatory postsynaptic currents (sEPSC and mEPSCs) were recorded in superficial DH neurons in acute spinal cord slices prepared from animals 5 days after sciatic nerve transection and in controls. RESULTS: In slices after axotomy the sEPSC frequency was 2.8 ± 0.8 Hz, while neurons recorded from slices after TNFα incubation had significantly higher sEPSC frequency (7.9 ± 2.2 Hz). The effect of TNFα treatment was smaller in the slices from the control animals, where sEPSC frequency was 1.2 ± 0.2 Hz in slices without and 2.0 ± 0.5 Hz with TNFα incubation. Tetrodotoxin (TTX) application in slices from axotomized animals and after TNFα incubation decreased the mEPSC frequency to only 37.4 ± 6.9% of the sEPSC frequency. This decrease was significantly higher than in the slices without the TNFα treatment (64.4 ± 6.4%). TTX application in the control slices reduced the sEPSC frequency to about 80% in both TNFα untreated and treated slices. Application of low concentration TRPV1 receptors endogenous agonist N-oleoyldopamine (OLDA, 0.2 μM) in slices after axotomy induced a significant increase in mEPSC frequency (175.9 ± 17.3%), similar to the group with TNFα pretreatment (158.1 ± 19.5%). CONCLUSIONS: Our results indicate that TNFα may enhance spontaneous transmitter release from primary afferent fibres in the spinal cord DH by modulation of TTX-sensitive sodium channels following sciatic nerve transection. This nerve injury also leads to enhanced sensitivity of presynaptic TRPV1 receptors to endogenous agonist. Modulation of presynaptic receptor activity on primary sensory terminals by TNFα may play an important role in neuropathic pain development.
Keywords: Synaptic Transmission; sodíkové kanály; Patch-Clamp Techniques; Male; Rats, Wistar; Tumor Necrosis Factor-alpha; Spinal Cord; Sodium Channels; Synapses; spinální ganglia; excitační postsynaptické potenciály; synapse; mužské pohlaví; metoda terčíkového zámku; potkani Wistar; nocicepce; Peripheral Nervous System Diseases; nervový přenos; krysa rodu Rattus; Neurons, Afferent; Animals; mícha; zvířata; Rats; nemoci periferního nervového systému; TNF-alfa; neurony aferentní; Ganglia, Spinal; Nociception; Excitatory Postsynaptic Potentials